PENGARUH MOTIVASI KERJA TERHADAP KINERJA APARATUR PEMERINTAH DAERAH DI KANTOR LINGKUNGAN HIDUP KABUPATEN KAYONG UTARA - Mya Novya E.42009072 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2021)
This script aims to determine how much influence the motivation to work on the performance of local government officials in the Environment Office of Northern Kayong District. This study related from social phenomena regarding work motivation of local government officials in the Ministry of Environment Office (KLH) of Northern Kayong District. Performance of local government officials in the Ministry of KLH Kayong District not considered optimal so needed the motivation in order to improve its performance. This study use quantitative research methods with 24 respondent. The results of the data analysis using the computer program Statistical Product and Service Solutions (SPSS) V.18. The result is a positive correlation between motivation to work on the performance of local government in the District of North Kayong KLH. Correlation coefficient of these two variables is equal to 0.868. Based coefficient value determination shows that there are significant performance motivation on employee performance in the District of North Kayong KLH by 75.4%, while 24.6% is influenced by other factors not examined in this study. Keywords: Work Motivation, Performance Local Government Reform.